Attention Modulation of Stimulus Rivalry under Swapping Paradigm. (May 2014) - Doualot, Audrey; Simard, Mathieu; Saint-Amour, Dave
Stimulus rivalry refers to the sustained periods of perceptual dominance that occur when different visual stimuli are swapped at a regular rate between eyes. This phenomenon is thought to involve mainly eye-independent mechanisms. Although several studies have reported that attention can increase image predominance in conventional binocular rivalry, it is unknown whether attention can specifically modulate stimulus rivalry. We addressed this question and manipulated the spatial characteristic of the stimuli to assess whether such an attention modulation could depend on visual processing hierarchy. The results showed that selective attention of stimulus rivalry significantly increased the predominance of the attended stimulus, regardless of the stimulus' spatial characteristics. No effect was observed on the swapping percept. The findings are discussed in the context of recent models attempting to characterize stimulus rivalry between eye-dependent and eye-independent levels.